MOF@PEDOT Composite Films for Impedimetric Pesticide Sensors. Issue 2 (8th January 2020) - Sappia, Luciano D.; Tuninetti, Jimena S.; Ceolín, Marcelo; Knoll, Wolfgang; Rafti, Matías; Azzaroni, Omar
Abstract: Due to its deleterious effects on health, development of new methods for detection and removal of pesticide residues in primary and derived agricultural products is a research topic of great importance. Among them, imazalil (IMZ) is a widely used post‐harvest fungicide with good performances in general, and is particularly applied to prevent green mold in citrus fruits. In this work, a composite film for the impedimetric sensing of IMZ built from metal‐organic framework nanocrystallites homogeneously distributed on a conductive poly(3, 4‐ethylene dioxythiophene) (PEDOT) layer is presented. The as‐synthetized thin films are produced via spin‐coating over poly(ethylene terephtalate (PET) substrate following a straightforward, cost‐effective, single‐step procedure. By means of impedance spectroscopy, electric transport properties of the films are studied, and high sensitivity towards IMZ concentration in the range of 15 ppb to 1 ppm is demonstrated (featuring 1.6 and 4.2 ppb limit of detection, when using signal modulus and phase, respectively). The sensing platform hereby presented could be used for the construction of portable, miniaturized, and ultrasensitive devices, suitable for pesticide detection in food, wastewater effluents, or the assessment of drinking‐water quality. Abstract : Development of portable devices for on‐site evaluation of pesticide residues remains a topic of great interest worldwide. With this aim, a chemi‐impedimetric sensor for imazalil is presented, based on metal–organic frameworks (MOFs) nanoparticles incorporated into conductive poly(3, 4‐ethylene dioxythiophene) (PEDOT) films. The impedimetric sensors are extremely sensitive to imazalil concentration in the range of 15 ppb to 1 ppm.